مساهمة معايير التدقيق الجزائرية في تحسين أداء المالي للمؤسسات دراسة ميدانية على مكاتب محافظي الحسابات ولاية الوادي - عبير وادي; إخلاص علال; حمزة سعداني (جامعة الوادي University of Eloued, 2025)
"هدفت هذه الدراسة الى التعرف على مدى مساهمة معايير التدقيق في تحسين الأداء المالي للمؤسسات وهذا من خلال دراسة ميدانية شملت عينة من المؤسسات بولاية الوادي، من خلال تعزيز مصداقية وشفافية المعلومات المالية، وضمان موثوقية التقارير المحاسبية، وتكتسي هذه المعايير أهمية بالغة في دعم فعالية عمليات التدقيق، خاصة في ضل بيئة اقتصادية تتطلب دقة عالية وامتثالا للمعايير المعترف بها دوليا. وقد تم التوصل من خلال هذه الدراسة الى أن اعتماد المعايير الجزائرية للتدقيق يساهم إيجابيا في تحسين الأداء المالي للمؤسسات، من خلال دعم آليات الرقابة الداخلية، وتوفير أدلة كافية وموثوقة تساعد المدقق في اصدار رأي مهني دقيق وموضوعي. "This study aimed to distinguish the extent to which the unification standards contribute to improving performance in an integrated manner, and this is through a field study to demonstrate the creativity of the valley, by enhancing the credibility and transparency of financial information, reliably known as the accounting report, and this is why we decided to support the effectiveness of auditing operations, especially in light of the high functional efficiency of distinguished obligations and recognition recognized by Sharia. This study concluded that adopting Algerian auditing standards contributes positively to improving the financial performance of institutions, by supporting internal control mechanisms and providing sufficient and reliable evidence that helps the auditor issue an accurate and objective professional opinion.
ماسترالعلوم المالية والمحاسبية
Keywords: معايير التدقيق الجزائرية; الأداء المالي; شفافية المعلومات; مصداقية القوائم المالية; Algerian auditing standards; financial performance; information transparency; reliability of financial statements.